Pemanfaatan Pekarangan Sebagai Strategi untuk Mewujudkan Ketahanan Pangan Keluarga - A. Muh. Arif Bijaksana; A. St. Fatmawaty; Luciana Buarlele; Ade Sugiarti Kumalasari (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2024)
Backyard land is one of the agricultural objects that is neglected and receives less attention while it can provide additional income for farming households. The emergence of the phenomenon of rising prices of basic commodities that have increased every time is certainly a problem for the community, especially for small communities. Kelurahan Maccini Baji is located in Maros Regency and is considered a self-sufficient area. Therefore, the village should be a agricultural superior and advanced. Agricultural is one of the key factors supporting the local economy, which is expected to support Kelurahan Maccini Baji to become a more independent area in terms of economy and food, including family food security. For the food needs of the community in Maccini Baji village, the PKM team then conducted socialization related to the use of yard land which is often considered trivial to be an alternative strategy to meet family food needs. It is important for the community to educated to be wiser in managing yard land as a source of daily food and creating better and halal nutritional quality. The utilization of yard land can economically reduce family costs and, if done seriously, can generate additional income.